FAKTOR PELECEHAN SEKSUAL DALAM PERSPEKTIF PEDIDIKAN ISLAM - indah, Dwi Indah Nursita; Hanin, Al Yani Hanin (Institut Agama Islam Uluwiyah Mojokerto Indonesia, 2023)
Harassment is defined as a pattern or offensive behavior that appears to have anunfavorable purpose towards the target person, sexual harassment is also a broadand complex issue of gender reactions and involves aspects of human life such asmorals, religion, faith and others. Sexual violence violates morals and religious values which are not only accounted forin this world,but also inthe here after. One of the effort stobuild awarenes sistosocialize that sexual violence is amajor crime that makes religion the main enemy besides God Almighty. As a religion that isnon-violent, it is not too difficult to conclude that Islam is one of the religions that also callsf orthe elimination of sexual violence, ranging from sexual harassmentt oslavery and sexual exploitation. Dozens of verses of the Koran are contained in itand build public awareness that violence against women is contrary to the valuesofmonotheismand al-karamah al-insaniyah.